2013
DOI: 10.1214/12-aoas597
|View full text |Cite
|
Sign up to set email alerts
|

Joint and individual variation explained (JIVE) for integrated analysis of multiple data types

Abstract: Research in several fields now requires the analysis of datasets in which multiple high-dimensional types of data are available for a common set of objects. In particular, The Cancer Genome Atlas (TCGA) includes data from several diverse genomic technologies on the same cancerous tumor samples. In this paper we introduce Joint and Individual Variation Explained (JIVE), a general decomposition of variation for the integrated analysis of such datasets. The decomposition consists of three terms: a low-rank approx… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
536
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(537 citation statements)
references
References 36 publications
1
536
0
Order By: Relevance
“…We foresee that the real potential for nutritional systems biology applications will lie in multiknowledge integration strategies that will, by including information at different levels, shed light on gene-nutrient interactions with a degree of accuracy and completeness not yet achievable today. Lock et al (2013) Multivariatebased integration…”
Section: Resultsmentioning
confidence: 99%
“…We foresee that the real potential for nutritional systems biology applications will lie in multiknowledge integration strategies that will, by including information at different levels, shed light on gene-nutrient interactions with a degree of accuracy and completeness not yet achievable today. Lock et al (2013) Multivariatebased integration…”
Section: Resultsmentioning
confidence: 99%
“…The method was recently used in a landmark study to predict novel breast cancer subtypes with distinct clinical outcomes (9), and it was found that the joint clustering of copy number and gene expression profiles resolved the considerable heterogeneity of the expression-only subgroups. Other approaches on data integration that have emerged in recent years include generalized data decomposition methods (10,11) and nonparametric Bayesian models (12). However, two major challenges have not yet been fully addressed.…”
mentioning
confidence: 99%
“…Matrix Factorization unsupervised JIVE [130] Cancer patient stratification by integrating mRNA expression and miRNA expression data. Network-based unsupervised SNF [131] Patient subtyping by integrating patient similarity networks constructed from mRNA expression, DNA methylation and miRNA expression data.…”
Section: Databasementioning
confidence: 99%